2014 International Conference on Smart Electric Grid (ISEG) 2014
DOI: 10.1109/iseg.2014.7005392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various methods for optimal placement of FACTS devices

Abstract: The Flexible AC Transmission System (FACTS) controllers play a vital role in the power system security enhancement. However, due to high capital investment, it is necessary to place these controllers at optimal locations in the power system. This paper presents comparison of various methods used for optimizing the location of Thyristor Controlled Series Compensators (TCSC) and Thyristor Controlled Phase Angle Regulators (TCPAR) which are FACTS devices. A sensitivity based approach has been used to decide optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…, @P i @Iq Iq¼0 and @P j @Iq Iq ¼0 can be derived using (40)- (45) respectively. The sensitivity factors c 1 u , c 2 u and c 3 u can be derived by partially differentiating PI w.r.t V T, d T and I q in line-k respectively.…”
Section: Methods 2: Real Power Flow Pi Sensitivity Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…, @P i @Iq Iq¼0 and @P j @Iq Iq ¼0 can be derived using (40)- (45) respectively. The sensitivity factors c 1 u , c 2 u and c 3 u can be derived by partially differentiating PI w.r.t V T, d T and I q in line-k respectively.…”
Section: Methods 2: Real Power Flow Pi Sensitivity Indicesmentioning
confidence: 99%
“…The proposed work is an extension of [45] in which the same generalized approach has been implemented to determine optimal Location of TCSC and TCPAR.…”
Section: Introductionmentioning
confidence: 99%
“…(36). Without change in principle, this is applicable for the determination of FACTS location in congestion management [39][40][41][42][43]. Accordingly, when power flow congestion limits the power transfer transaction, Eq.…”
Section: Formation Of Reduced Search Space For Facts Locationmentioning
confidence: 99%
“…There is a substantial extant literature on locating power electronics devices to improve power system operation (partial reviews can be found in [12,13,14,15]). Such devices can be located in power systems using diverse strategies and in pursuit of various objectives.…”
Section: Introductionmentioning
confidence: 99%